Metabolomics and amino acid profiling of plasma reveals the metabolite profiles associated with nitrogen utilisation efficiency in primiparous dairy cows - H. Li; S.K. La; L.Y. Zhang; S. Li; Z.B. Yu; L.M. Ao; T.Y. Gao; H.T. Huang (Animal, 2024)
Nitrogen (N) utilisation efficiency (NUE, milk N yield [g/d]/N intake [g/d]) is an important performance indicator in dairy farming. Determining the NUE-associated blood metabolite profile will contribute to the optimisation of nutritional strategies to further improve NUE among dairy cows. Here, 20 primiparous lactating cows with days in milk ranging from 95 to 115 days were selected from a total of 1 221 cows. Each cow’s N intake and milk N yield were measured for 7 days. Subsequently, blood samples were collected before morning feeding. Based on analysis and calculations, cows were retrospectively classified into two groups based on their NUE values, namely, a low NUE group (LNUE, NUE = 24.8 ± 1.6%, n = 10, mean ± SD) and a high NUE group (HNUE, NUE = 35.2 ± 1.7%, n = 10, mean ± SD). Plasma samples were selected from six cows in each group for metabolomics and amino acid profiling. Among the 41 differential metabolites (DMs) identified in the metabolomic analysis, sucrose, MG(0:0/22:1(13Z)/0:0), 2-amino-6-hydroxyhexanoic acid, and L-glutamine exhibited significant correlations with NUE, milk yield, and BW (P < 0.05). Moreover, the five differential amino acids and amino acid metabolites (DAAs) identified in the amino acid profiling and 5 of the 6 differential amino acids and amino acid conjugates identified by plasma metabolomics were found to be less abundant in the HNUE group (P < 0.05). Specifically, there was a 39.4% decrease in L-arginine content and a 29.2% decrease in L-glutamine content (P < 0.05). Pathway analysis indicated that the DMs and DAAs were mainly involved in arginine biosynthesis, glutathione metabolism, arginine and proline metabolism, and tryptophan metabolism (pathway impact > 0.1). These results provided new insights into the new blood metabolite profile associated with NUE in dairy cows. These new insights can provide foundational information for the formulation of new strategies to further enhance NUE in dairy cows.